2004
DOI: 10.1111/j.1463-1326.2004.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ezetimibe co‐administered with simvastatin in thiazolidinedione‐treated type 2 diabetic patients

Abstract: Co-administration of ezetimibe with simvastatin, a dual inhibition treatment strategy targeting both cholesterol synthesis and absorption, is well tolerated and provides greater LDL-C-lowering efficacy than increasing the dose of simvastatin in T2DM patients taking TZDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 40 publications
5
39
0
Order By: Relevance
“…This is in agreement with the findings of Gaudiani et al [4], showed that despite the absolute lower values of hs-CRP in the statin plus ezetimibe group, there were no significant variations, neither for hs-CRP, nor for fibrinogen. On contrary, another study [5] showed that hs-CRP, was reduced by 18.2% with simvastatin monotherapy and 34.8% with the co administration of ezetimibe.…”
supporting
confidence: 93%
“…This is in agreement with the findings of Gaudiani et al [4], showed that despite the absolute lower values of hs-CRP in the statin plus ezetimibe group, there were no significant variations, neither for hs-CRP, nor for fibrinogen. On contrary, another study [5] showed that hs-CRP, was reduced by 18.2% with simvastatin monotherapy and 34.8% with the co administration of ezetimibe.…”
supporting
confidence: 93%
“…This finding indicates the treatment effects were similar in direction to the overall study results and consistently favored EZE/SIMVA therapy even when compared with the highest-potency statin regimens (that is, atorvastatin 40 and 80 mg; rosuvastatin 20 and 40 mg, and SIMVA 80 mg). In several prior studies conducted in patients already taking statin therapy but not at their LDL-C goal, adding EZE was shown to be more effective at lowering LDL-C compared with doubling the statin dose [28,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] These significantly greater effects have also been shown with ezetimibe added to the moderate doses of statins compared with doubling the dose of the same statin in moderately-high risk and high-risk CHD patients and in diabetic patients. [20][21][22] This study assessed the lipid-altering efficacy and tolerability of 6 weeks of treatment with ezetimibe/simvastatin 10/20 mg versus doubling the dose of simvastatin to 40 mg in patients with hypercholesterolemia and established CHD who had not achieved the National Cholesterol Education Program Adult Treatment Panel III recommended LDL-C target less than 100 mg/dL while being treated with a daily dose of simvastatin 20 mg.…”
mentioning
confidence: 99%